2021
DOI: 10.1021/acsomega.1c00773
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Detection of Morphine in Untreated Human Capillary Whole Blood

Abstract: Disposable single-use electrochemical sensor strips were used for quantitative detection of small concentrations of morphine in untreated capillary whole blood. Single-walled carbon nanotube (SWCNT) networks were fabricated on a polymer substrate to produce flexible, reproducible sensor strips with integrated reference and counter electrodes, compatible with industrial-scale processes. A thin Nafion coating was used on top of the sensors to enable direct electrochemical detection in whole blood. These sensors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Notably, tiny amperage responses of Cys (7.5%) and DA (8.9%) are observed as compared to AA, indicating its negligible interference effect. Since the maximum tolerance level of the interferents is taken to be 100-fold higher than AA, it can give rise to an approximately ±10% relative error and thus not have any influence during the determination of AA . The appearance of a small peak followed by the steady response of Cys can be a result of diffusion in the electrochemical system .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, tiny amperage responses of Cys (7.5%) and DA (8.9%) are observed as compared to AA, indicating its negligible interference effect. Since the maximum tolerance level of the interferents is taken to be 100-fold higher than AA, it can give rise to an approximately ±10% relative error and thus not have any influence during the determination of AA . The appearance of a small peak followed by the steady response of Cys can be a result of diffusion in the electrochemical system .…”
Section: Resultsmentioning
confidence: 99%
“…Since the maximum tolerance level of the interferents is taken to be 100-fold higher than AA, it can give rise to an approximately ±10% relative error and thus not have any influence during the determination of AA. 65 The appearance of a small peak followed by the steady response of Cys can be a result of diffusion in the electrochemical system. 66 Previously, Wu et al 67 reported that generation of the tiny response of Cys can be attributed to the surface complexes formed between the active oxygencontaining groups of erGO, especially the aldehyde groups and the N-terminal Cys.…”
Section: 24mentioning
confidence: 99%
“…5 Moreover, electrochemical test strips enable analysis of small complex biological samples, such as whole blood, with minimal 6 or no sample treatment. 7 Recently, we described the production of single-walled carbon nanotube/Nafion-based test strips (SWCNT/Nafion) with industrial high throughput methods.…”
Section: Introductionmentioning
confidence: 99%
“…Paracetamol can be readily detected with electrochemical methods 4 and it is well suited to point‐of‐care (POC) analysis, given the availability of inexpensive and easy‐to‐use portable potentiostats 5 . Moreover, electrochemical test strips enable analysis of small complex biological samples, such as whole blood, with minimal 6 or no sample treatment 7 . Recently, we described the production of single‐walled carbon nanotube/Nafion‐based test strips (SWCNT/Nafion) with industrial high throughput methods.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past few decades, researchers from different fields have shown an increasingly growing interest in the determination of drugs present in clinical, environmental and pharmaceutical samples with a view to tackling the problems related to drug intoxication and wastewater contamination as well as ensuring the quality control of pharmaceutical products [ 1 ]. This has resulted in the development of several techniques with accurate tools targeted at the qualitative (simple yes/no analysis) and/or quantitative determination of drugs at trace levels in different samples (including urine, serum and water).…”
Section: Introductionmentioning
confidence: 99%